Conductive composition containing perfluoropolyether oil and carbon nanotubes

The conductive composition of perfluoropolyether oil and carbon nanotubes addresses the challenge of high impedance and electrocorrosion in rolling bearings by enhancing current flow and reducing voltage differences, achieving effective electrocorrosion suppression and improved operational stability.

JP2025065620APending Publication Date: 2025-04-22KYODO YUSHI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023174937
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing conductive compositions for rolling bearings and similar applications fail to effectively manage current flow in AC circuits, leading to high impedance and potential electrocorrosion due to voltage differences between rotating parts.

Method used

A conductive composition combining perfluoropolyether oil with carbon nanotubes of specific diameters (0.4 to 5.0 nm) and concentrations (0.5 to 3.0% by mass), which reduces impedance and suppresses electrocorrosion by enhancing current flow in AC circuits.

Benefits of technology

The composition achieves reduced impedance, maintaining a good current-power state, suppressing electric charge accumulation and discharge, and thereby preventing electrocorrosion, while also lowering breakdown voltage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025065620000004
    Figure 2025065620000004
  • Figure 2025065620000001
    Figure 2025065620000001
  • Figure 2025065620000002
    Figure 2025065620000002
Patent Text Reader

Abstract

To provide a conductive composition with a low impedance.SOLUTION: The present invention provides a conductive composition that contains a perfluoropolyether oil as a base oil and carbon nanotubes as a conductive substance, wherein the diameter of the carbon nanotubes is 0.4-5.0 nm and the content of the carbon nanotubes is 0.5-3.0 mass% relative to the total mass of the composition.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an electrically conductive composition that can be used in rolling bearings and the like. [Background technology]

[0002] In recent years, variable speed operation of rotating electrical machines using inverter power sources has been used in the fields of automobiles, railways, home appliances, and the like. However, electrical problems have also arisen with inverter drive. For example, in bearings, damage called electrolytic corrosion occurs when a voltage is applied between the rotating shaft and the bearing, causing discharge. In the case of bearings, electrolytic corrosion occurs when there is a potential difference between the inner and outer rings of the bearing, or when a common mode current flows. In more detail, electrolytic corrosion progresses due to continuous discharge in the lubricating film interposed between the balls, which are the rolling elements of the bearing, and the raceway surface of the bearing.

[0003] Patent Document 1 aims to provide a conductive grease that exhibits good electrical conductivity and also has good friction properties, and provides a conductive grease that contains perfluoropolyether oil as a base oil and 0.1 to 20 weight % of carbon nanotubes having a diameter of 40 to 200 nm as a conductivity-imparting substance. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Patent No. 5747230 Summary of the Invention [Problem to be solved by the invention]

[0005] In Patent Document 1, the superiority or inferiority of electrical conductivity is evaluated by the value of volume resistivity. Although the volume resistivity is a value calculated by measurement using a DC circuit, it is more appropriate to evaluate the difficulty of current flow in an inverter circuit that converts DC to AC, that is, an index equivalent to resistance, by impedance, which indicates the difficulty of current flow in an AC circuit. An object of the present invention is to provide a conductive composition having low impedance. [Means for solving the problem]

[0006] The present invention provides the following conductive composition. 1. Contains perfluoropolyether oil as a base oil and carbon nanotubes as a conductive material. The carbon nanotube has a diameter of 0.4 to 5.0 nm, and A conductive composition, wherein the content of the carbon nanotubes is 0.5 to 3.0% by mass based on the total mass of the composition. 2. The conductive composition according to 1, wherein the carbon nanotubes are single-walled or double-walled. 3. The conductive composition according to 1 or 2, which does not contain a thickener. 4. The conductive composition according to 1 or 2, further comprising a thickener. Effect of the Invention

[0007] According to the present invention, by combining a specific amount of perfluoropolyether oil and carbon nanotubes of a specific size, the impedance value, which indicates the difficulty of current flow in an AC circuit, can be reduced. As a result, the conductive composition can maintain a good current flow state and suppress discharge by making it difficult for electric charges to accumulate, so the conductive composition of the present invention can suppress the occurrence of electrolytic corrosion. The composition of the present invention can also reduce the dielectric breakdown voltage. [Brief description of the drawings]

[0008] [Figure 1] 1 is a schematic diagram showing the overall structure of a carbon nanotube; DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] <Base oil> Specific examples of perfluoropolyether oils that can be used in the composition of the present invention include those represented by the formulas (1) to (5). Among these, the one represented by the formula (1) is particularly preferred.

[0010] [ka]

[0011] The perfluoropolyether oil of the present invention can be used alone or in combination of two or more kinds, but does not include base oils other than the perfluoropolyether oil. Kinematic viscosity at 40°C (measured according to JIS K2283) is approximately 4 to 2000 mm 2 More preferably, the kinetic viscosity is 60 to 500 mm 2 / s. The kinetic viscosity of the base oil at 40°C is 4mm 2 If the kinematic viscosity at 40°C is 2000mm / s or more, the evaporation of the base oil and oil separation at high temperatures tend to be suppressed, which is preferable. 2 / s or less is preferable because it is easier to obtain appropriate fluidity. Also, perfluoropolyether oils having a relatively high kinetic viscosity at 40°C, e.g. 2 When a perfluoropolyether oil having a kinetic viscosity of 40° C. or more is used, the conductive composition of the present invention can be made into a paste-like form, which prevents leakage or dripping at the application site and improves usability depending on the application. As will be described later, a thickener and / or a solid lubricant can be added to the conductive composition of the present invention to make it into a solid or semi-solid grease-like form. In this case, a perfluoropolyether oil having a relatively low kinetic viscosity at 40° C., for example 400 mm 2 It may also be a perfluoropolyether oil having a viscosity of 1 / s or less. The content of the perfluoropolyether oil in the conductive composition of the present invention is preferably 50 to 99.5 mass %, more preferably 60 to 99.4 mass %, and even more preferably 70 to 99.3 mass %, based on the total mass of the composition. The content of the base oil in such a range is preferable from the viewpoints of fluidity and heat resistance.

[0012] <Carbon nanotubes> Carbon nanotubes are tubes made of stacked graphite-like carbon, with both ends of each layer closed like fullerenes. The overall structure is roughly as shown in Figure 1. The minimum diameter ("D") of carbon nanotubes reported so far is 0.4 nm (Lu-Chang Qin et al., "The smallest carbon nanotube", Nature, 408, 50 (2000)). In the present invention, carbon nanotubes with a diameter of 0.4 nm or more can be used. On the other hand, since the torque increases as the content of carbon nanotubes in the composition increases, it is preferable that the content of carbon nanotubes in the composition is small. By containing carbon nanotubes with a diameter of 5.0 nm or less, a sufficient discharge suppression effect can be exhibited even in a small amount. The composition of the present invention preferably contains carbon nanotubes with a diameter of 0.4 to 5.0 nm, and more preferably contains carbon nanotubes with a diameter of 1.2 to 5.0 nm. On the other hand, in carbon nanotubes with a diameter of more than 5.0 nm, multi-walled carbon nanotubes with three or more walls account for a large proportion, which makes it easy to discharge, so it is preferable that the conductive composition of the present invention does not contain carbon nanotubes with a diameter of more than 5.0 nm.

[0013] The length of the carbon nanotube is not particularly limited. For example, carbon nanotubes having a length of 5 μm or more and 600 μm or less can be used. The diameter of a carbon nanotube refers to the short side in plan view, and the length of a carbon nanotube refers to the long side in plan view, as shown in Figure 1. The diameter and length of a carbon nanotube can be measured using a transmission electron microscope.

[0014] Generally, carbon nanotubes are available in single-wall, double-wall, and triple-wall or more multi-wall configurations, but the carbon nanotubes used in the conductive composition of the present invention are preferably single-wall or double-wall from the viewpoint of discharge suppression effect. From the viewpoint of discharge suppression effect, the conductive composition of the present invention is preferably substantially free of triple-wall or more multi-wall carbon nanotubes. For example, based on the total mass of the composition, the content is preferably 0.5 mass% or less, more preferably 0.2 mass% or less, and even more preferably 0.1 mass% or less. The carbon nanotubes have active sites on the surface, at least a part of which may be modified with OH, CH, CHO, etc. However, as the carbon nanotubes used in the present invention, unmodified ones are preferable because they have a higher affinity with the base oil.

[0015] The content of carbon nanotubes in the conductive composition of the present invention is 0.5 to 3.0 mass% based on the total mass of the composition, preferably 0.6 to 2.0 mass%, more preferably 0.7 to 1.5 mass%. When the content of carbon nanotubes is in such a range, it is preferable because the discharge suppression effect is effectively exhibited. By adding about 0.5% by mass of carbon nanotubes having a diameter of 0.4 to 5.0 nm to the perfluoropolyether oil, the composition of the present invention has a hardness equivalent to a 60-stroke worked penetration (measured according to JIS K 2220 7.) of about 440 in terms of grease. On the other hand, by adding about 3.0% by mass of carbon nanotubes having a diameter of 0.4 to 5.0 nm, the composition of the present invention has a hardness equivalent to the above-mentioned penetration of about 200. Note that, in the case of grease, a penetration of less than 200 is generally not possible (because if it is too hard, the grease cannot flow into the lubricated part), but the composition of the present invention can be used in places where lubrication is not required as long as prevention of electrolytic corrosion is required. In this case, the hardness may be equivalent to a penetration of less than 200.

[0016] If necessary, the conductive composition of the present invention may further contain a thickener, a solid lubricant, an antioxidant, a rust inhibitor, an extreme pressure agent, an oiliness agent, etc. Among these, it is preferable to contain a thickener from the viewpoint of oil retention and heat resistance.

[0017] <Thickener> By adding a thickener, the conductive composition of the present invention can be made into a grease, which is preferable from the viewpoints of oil retention and heat resistance. The thickener usable in the present invention may be any organic or inorganic thickener commonly used in fluorine-based greases, of which polytetrafluoroethylene is preferred from the viewpoint of its affinity with fluorine oil. Those skilled in the art can appropriately determine the consistency of the grease depending on the application. For example, when applied to bearings, the consistency is typically 220 to 340, and preferably 235 to 325. The content of the thickener is the amount required to obtain this consistency, and is, for example, 1 to 30 mass %, and preferably 5 to 15 mass %, based on the total mass of the grease composition.

[0018] <Solid lubricants> By incorporating a solid lubricant, the conductive composition of the present invention can be made into a grease or a compound. Examples of solid lubricants that can be used in the present invention include melamine cyanurate, graphite, onion-like carbon, nanodiamond, graphite fluoride, black silica, granular polyethylene, granular polypropylene, polyethylene wax, polypropylene wax, oxidized polyethylene wax, ester wax, montanic acid wax, amide wax, spherical alumina, zinc oxide, mica, molybdenum disulfide, tungsten disulfide, calcium carbonate, boron nitride, and metal powders such as copper and nickel. Among these, melamine cyanurate is preferred from the viewpoint of lubricity at high temperatures. The content of the solid lubricant is, for example, 0.01 to 5.0 mass %, and preferably 0.1 to 1.0 mass %, based on the total mass of the composition.

[0019] <Antioxidants> By including an antioxidant, it is possible to suppress the oxidative deterioration of the grease. The antioxidants that can be used in the present invention include phenol-based antioxidants and amine-based antioxidants. Examples of phenol-based antioxidants include 2,6-di-tert-butyl-p-cresol (BHT), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 2,6-di-tert-butyl-phenol, 2,4-dimethyl-6-tert-butylphenol, tert-butylhydroxyanisole (BHA), 4,4'-butylidenebis(3-methyl-6-tert-butylphenol), 4,4'-methylenebis(2,3-di-tert-butylphenol), 4,4'-thiobis(3-methyl-6-tert-butylphenol), and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate. Of these, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate is preferred from the viewpoints of volatility and oil resistance. Examples of the amine-based antioxidant include Nn-butyl-p-aminophenol, 4,4'-tetramethyl-di-aminodiphenylmethane, α-naphthylamine, N-phenyl-α-naphthylamine, phenothiazine, alkyldiphenylamines, etc. Among these, alkyldiphenylamines are preferred from the viewpoints of both the effectiveness of suppressing sludge formation and viscosity increase and the cost. The content of the antioxidant is, for example, 0.01 to 5.0 mass %, and preferably 0.1 to 1.0 mass %, based on the total mass of the composition.

[0020] <Rust inhibitor> By including a rust inhibitor, the occurrence of rust on the lubricated surface can be prevented. The rust inhibitors that can be used in the present invention include inorganic rust inhibitors and organic rust inhibitors. Examples of inorganic rust inhibitors include inorganic metal salts such as sodium silicate, lithium carbonate, potassium carbonate, and zinc oxide. Examples of organic rust inhibitors include sodium benzoate, benzoates of lithium benzoate, zinc naphthenate, carboxylates of sodium sebacate, succinic acid, succinic anhydride, succinic acid derivatives of succinic acid half esters, fatty acid amine salts, benzotriazole or derivatives thereof, benzothiazole or derivatives thereof, and thiadiazole or derivatives thereof. Of these, sodium sebacate is preferred because it exerts an excellent effect even in small amounts. The content of the rust inhibitor is, for example, 0.01 to 5.0 mass % and preferably 0.1 to 1.0 mass % based on the total mass of the composition.

[0021] <Extreme pressure agent> By including extreme pressure agents, it acts to reduce friction and wear between two metal surfaces and to prevent seizure. Examples of extreme pressure agents that can be used in the present invention include chlorine compounds such as sulfurized oils and fats, sulfurized olefins, polysulfides, ashless dithiocarbamates, trioctyl phosphate, tricresyl phosphate, triphenyl phosphorothioate, zinc dialkyldithiocarbamates, dialkyldithiocarbamates of molybdenum dialkyldithiocarbamates, zinc dialkyldithiophosphates, dialkyldithiophosphates of molybdenum dialkyldithiophosphates, chlorinated paraffins, and chlorinated diphenyls. Among these, dialkyldithiocarbamates and dialkyldithiophosphates are preferred from the viewpoint of suitability under high temperature and high load conditions. The content of the extreme pressure agent is, for example, 0.01 to 5.0 mass %, and preferably 0.1 to 1.0 mass %, based on the total mass of the composition.

[0022] <Oil-based agent> By including an oily agent, it prevents direct contact between metal and metal, thereby reducing friction and wear. Examples of oiliness agents that can be used in the present invention include fatty acids or their esters, higher alcohols, polyhydric alcohols or their esters, aliphatic esters, aliphatic amines, fatty acid monoglycerides, montan wax, amide waxes, etc. Among these, montan wax is preferred from the viewpoint of suitability under normal temperature and low load conditions. The content of the oily agent is, for example, 0.01 to 5.0 mass %, and preferably 0.1 to 1.0 mass %, based on the total mass of the composition.

[0023] The composition of the present invention can be easily produced by adding perfluoropolyether oil, carbon nanotubes, and, if necessary, optional components, and mixing them uniformly. Examples of such methods include a method of kneading while heating using a planetary mixer, etc., and further kneading uniformly using a three-roll mixer, and a method of kneading using a mixer that rotates and revolves to knead (hereinafter referred to as a "rotating and revolving mixer"). The composition of the present invention can be used for rolling bearings and the like. EXAMPLES

[0024] The conductive compositions of the examples and comparative examples were prepared as follows. That is, the base oil and carbon nanotubes were placed in a planetary centrifugal mixer "Awatori Rentaro ARE-310" (manufactured by Thinky Corporation) so as to have the components and contents shown in Table 1, and mixed at 25°C and a revolution speed of 1400 rpm for 10 minutes. Then, the impedance of the composition was measured by the following method.

[0025] <Impedance measurement> The impedance was measured using an LCR meter "IM3536" (manufactured by HIOKI), and the impedance values ​​at an AC frequency of 100,000 Hz (100 kHz) are shown in Table 1. [Measurement conditions] Measurement temperature: 25℃ AC frequency: 10~1000000(1M)Hz Measurement voltage: 0.2V Conductive composition thickness: 2mm Diameter of conductive composition: 20mm

[0026] The base oils used in the examples and comparative examples are as follows. PFPE: Solvay's "Fomblin YPL1500" (dynamic viscosity @ 40℃ = 420mm 2 / s) PAO: Polyαolefin (Kinematic viscosity @ 40℃ = 48mm 2 / s) The carbon nanotubes used in the examples and comparative examples are as follows.

[0027] [Table A]

[0028] [Table 1]

Claims

1. The oil contains perfluoropolyether oil as a base oil and carbon nanotubes as a conductive material, The carbon nanotubes have a diameter of 0.4 to 5.0 nm, and The conductive composition has a carbon nanotube content of 0.5 to 3.0 mass % based on the total mass of the composition.

2. The conductive composition of claim 1 , wherein the carbon nanotubes are single-walled or double-walled.

3. The conductive composition according to claim 1 or 2, which does not contain a thickener.

4. The conductive composition according to claim 1 or 2, further comprising a thickener.

Citation Information

Patent Citations

  • Alarm generator for automobile

    JP1982047230A